Petroleum conservation in the United States : an economic analysis - McDonald, Stephen L. (Baltimore ; London : Published for Resources for the Future by the Johns Hopkins Press, 1971)
The author develops an economic framework for analyzing state regulation of oil and gas and concludes that existing regulations fall short of assuring optimum well spacing, production rates, use of associated gas, and exploration.
Includes bibliographical footnotes and index.
kjo 17/01/2019
Loans
Keywords: Petroleum industry and trade; Petroleum law and legislation; Petroleum conservation